Plan de mejoramiento continuo para la empresa ALTEC S.A. en la ciudad de Babahoyo; Provincia de Los Ríos - Gómez Romero, Magaly Tatiana (2020)
This investigation was done in ALTEC S.A. from Babahoyo because of the interest in improving its performance by dealing with its processes, which have not been formally identified nor designed to make easier the right execution of the staff responsibilities. The before said problem is a situation that also occurs in other companies in Ecuador, mainly micro and small companies, where is required the establishment of a continuous improvement culture that allows sustainability and guarantees competitivity in the market. In the development of the investigation it was carried out a bibliographical and field study to get information to strength the research and validate the problem and the proposal. The research applied the qualitative and quantitative mode, made also use of a documental analysis and the application of techniques as the survey to clients and employees. Finally, once the data was processed it was proposed a plan for continuous improvement for the company specially directed to the most important processes.